(untitled) (Research, Society and Development, 2020)
Chemical compounds from the secondary metabolism of a plant, termed as allelochemicals, may interfere with the germination and/or development of other plant species, a phenomenon known as allelopathy. The aim of this study was to analyze the allelopathic potential of the Senna cearensis Afr. Fern. aqueous extract at various concentrations, collected from an area in the Chapada do Araripe during two different seasons (dry and rainy), on Lactuca sativa L. and Cenchrus echinatus L. seeds and seedlings, in addition to analysing the extract’s phytochemical prospection. The bioassays were conducted in a germination chamber at 25 °C with a 12h photoperiod and consisted of four treatments (extract at 12.5%, 25%, 50% and 100%) and a control group (distilled water). The variables analyzed were: seed germination, germination speed index, radicle length and caulicle seedling length. The means from each variable were submitted to an analysis of variance and compared using Tukey’s test (p<0.05), through the ASSISTAT. Quantitative prospection of the extract was performed using HPLC-DAD. The extracts reduced L. sativa seed germination, however it did not affect C. echinatus seeds. The extracts caused a reduction in germination rate and presented inhibitory effects on seedling development for both receptor species. Quercitrin was the major compound in both extracts. The allelopathic activity of the S. cearensis aqueous leaf extract collected during dry or rainy periods may be a viable alternative for weed control. Further studies addressing fractionation for separation and the possible isolation of substances responsible for the observed allelopathic activity are necessary.